Pengaruh Disiplin Kerja dan Semangat Kerja Terhadap Produktivitas Kerja Karyawan pada Bank Syariah Indonesia (Studi Pada Bank Syariah Indonesia Kota Pasuruan) - Niken Ardhiyati; Dyah Pikanthi Diwanti (Jurnal Bisnis, Manajemen, dan Akuntansi, 2023)
The study aimed at determining and testing the effect of work discipline on productivity, the effect of work enthusiasm on productivity, and how both work discipline and enthusiasm affect employees’ productivity at Bank Syariah Indonesia, Pasuruan. This study used a quantitative approach. The primary data used was a questionnaire with a total sample of 44 respondents. The sampling technique was non-probability sampling with a saturated census method. The data analysis included descriptive statistics, double regression analysis, correlation coefficient (R), determination coefficient (R2), f-test (simultaneous), and t-test (partial) with the help of the SPSS 21.0 for Windows program. The results of the study showed that; work discipline had a positive and significant partial effect on employee productivity with a t-value of 2.536 < 2.018 and Sig. of 0015 < 005; work enthusiasm had a positive and significant partial effect on employee productivity with a t-value of 4.586 < 2.018 and Sig. of 0.000 < 0.05; the value of the correlation coefficient of the work discipline and enthusiasm variables was 50.7% with the r2 value of 0.507 on employee work productivity at Bank Syariah Indonesia, Pasuruan which was proven to be in a strong category.